Infrared‐Assisted Synthesis of Prebiotic Glycine. Issue 6 (14th February 2020) - Scuderi, Debora; Pérez‐Mellor, Ariel; Lemaire, Joël; Indrajith, Suvasthika; Bardaud, Jean‐Xavier; Largo, Antonio; Jeanvoine, Yannick; Spezia, Riccardo
Abstract: A novel approach has been developed to synthesize complex organic molecules (COMs) relevant to prebiotic chemistry, using infrared (IR) radiation to trigger the reaction. An original laboratory reactor working at low gas density and using IR irradiation was developed. In this way, glycine, the simplest brick of life, has been synthesized by assisting ion–molecule reaction with IR laser light. The ion‐molecule complex constituted by acetic acid and hydroxylamine was formed in a mass spectrometer reactor and then irradiated with IR photons. As photoproducts, we obtained both glycine structures and some of its isomers. Anharmonic vibrational frequency calculations and fragmentation dynamics simulations allow for a better interpretation of the experimental data. This novel approach can be now extended to study other new synthetic pathways responsible for the formation of further COMs also with potential prebiotic relevance. Abstract : Triggered by IR : Glycine was synthetized under low‐density conditions assisted by IR photons.